Spiritual Struggles and Religious Cognitive Behavioral Therapy: A Randomized Clinical Trial in those with Depression and Chronic Medical Illness. Issue 1 (March 2016) - Pearce, Michelle J.; Koenig, Harold G.
Objectives: Compared the effectiveness of religious cognitive-behavioral therapy (RCBT) versus conventional CBT (CCBT) on reducing spiritual struggles in persons with major depressive disorder (MDD) and medical illness. Methods: Participants were randomized to receive 10 sessions of RCBT (n = 65) or CCBT (n = 67). Spiritual struggles were assessed at baseline, 12, and 24 weeks using the Brief RCOPE. Mixed effects growth curve models compared the effects of treatment on change in spiritual struggles. Results: RCBT and CCBT reduced spiritual struggles to a similar degree over time (B = −0.48, SE = 0.31, df = 151, t = −1.53, p = .127, d = 0.25). Similar results were found in those with high religiosity and with high spiritual struggles at baseline. Higher baseline spiritual struggles predicted a slower decline in MDD (B = 0.47, SE = 0.20, t = 2.30, p = .022) independent of treatment group. Conclusions: RCBT and CCBT are equally effective in reducing spiritual struggles in persons with MDD and medical illness. High spiritual struggles decrease the response of MDD to both RCBT and CCBT. These findings have treatment implications.